Unraveling biomolecules, antidiabetic and antioxidants properties of DelitesTM via pharmacoinformatics and in vitro investigation - Juan Leonardo; Purnawan Pontana Putra; Trina Ekawati Tallei; Fatimawali Fatimawali; Nurpudji Astuti Taslim; Raymond Rubianto Tjandrawinata; Vincent Lau; Saad Mustafa; Miguel A Prieto; Fahrul Nurkolis (Elsevier, 2024)
Introduction: Type 2 diabetes (T2D) remains a global health burden characterized by insulin resistance and chronic hyperglycemia, often exacerbated by oxidative stress, leading to severe complications. Despite the efficacy of pharmacological treatments such as metformin, their side effects and costs highlight the need for alternative therapies. Delites™ (Chong Cao Ling Zhi Xiang Tang), a multi-herbal formulation, presents a promising solution with its bioactive compounds including Apocynin, Curcumin, and Quercetin, which are hypothesized to target T2D pathways. Methods: This study employed pharmacoinformatics, in vitro assays, and molecular dynamics simulations to evaluate the antidiabetic and antioxidative properties of Delites™. Metabolomic profiling using Ultra-High-Performance Liquid Chromatography coupled with High-Resolution Mass Spectrometry identified active compounds, while in silico docking analyzed interactions with T2D-related proteins (e.g., KCNJ11, TCF7L2). Enzyme inhibition assays measured alpha-glucosidase and alpha-amylase activity, and antioxidant potential was assessed using ABTS inhibition. Results: Delites™ demonstrated significant enzyme inhibition (EC50 < metformin), strong binding affinity to T2D proteins (e.g., Sachaliside 2: -9.4 kcal/mol with TCF7L2), and antioxidant activity comparable to Trolox (EC50: 54.44 mg/mL). Molecular dynamics confirmed stable interactions of its compounds with target proteins, while network pharmacology highlighted multi-target potential against diabetes-related pathways. Discussion: The findings underline Delites™ as a multi-target therapeutic candidate for T2D management. Its ability to inhibit carbohydrate-hydrolyzing enzymes, interact strongly with key proteins, and mitigate oxidative stress positions it as a holistic alternative. However, further clinical trials are essential to validate these promising in vitro and in silico results, particularly its long-term efficacy and safety.